CD121b-positive neutrophils predict immunosuppression in septic shock - Chen, Jian; Zhang, Jinghe; Chen, Siao; Qin, Jingkun; Hu, Xinyu; Xi, Shengdi; Zhang, Lin; Zhou, Min; Zhou, Yonggang; Fu, Binqing; Wei, Haiming (Frontiers in Immunology, 2025)
BackgroundSeptic shock is linked with high mortality and significant long-term morbidity in survivors. However, the specific role of neutrophils in septic shock pathophysiology remains scarce in recent research.MethodsPeripheral blood immune cells from healthy donors and patients with septic shock were analyzed using single-cell RNA sequencing and batch RNA sequencing. We measured serum CD121b in both patients and healthy donors. Peripheral immune cells were isolated and exposed to either a CD121b recombinant protein or a CD121b blocking antibody to evaluate the expression of inflammatory factors. Additionally, in a humanized mouse sepsis model, the expression of CD121b in neutrophils across different tissues was assessed following treatment with all-trans retinoic acid (ATRA).ResultsThis study identified a subset of CD10-CD121b+ neutrophils in the peripheral blood of patients with septic shock. These patients exhibited elevated concentrations of soluble CD121b in serum and urine. Furthermore, outcomes revealed that the presence of CD121b+ neutrophils positively correlated with the severity of septic shock. These cells displayed immunosuppressive characteristics; after blocking CD121b, proinflammatory cytokines increased in peripheral immune cells. Additionally, we found that treatment with ATRA down-regulated the expression of CD121b.ConclusionsCD121b is closely associated with the progression of septic shock and may serve as a potential predictor indicator of immunosuppression for the condition.